Peran Kepribadian Anchor Virtues terhadap Flourishing pada Dosen PNS - Rahmatika, Aufilana; Hapsari, Maharani Tyas Budi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Personality plays a crucial role in influencing an individual's level of flourishing by the subject lecturers in the civil employee. One approach to understanding personality in the flourishing context is the concept of "anchor virtues." Anchor virtues are fundamental character traits that guide an individual's behavior and attitude. Civil servant lecturers with anchor virtue personalities are likelier to achieve a higher level of flourishing. This research aims to determine the role of anchor virtue personality in flourishing among civil servant lecturers. This study employs a quantitative method using a survey approach. The scales used include the modified Anchor Personal Inventory (API) with 13 valid items (α = 0,823) and a modified version of the PERMA scale with 29 valid items (α = 0,870). The researchers conducted classical assumption tests with 102 respondents who are Indonesian citizens working as lecturers in Surakarta, aged between 25 and 30 years. Classical assumption tests included normality and linearity tests. The hypothesis was then performed using simple linear regression. The results of this research are the results of linear regression analysis showing that anchor virtues predict flourishing significantly (p <0.000). Anchor virtues contributed to changes in flourishing by 51,4% (R2 = 0.514). Thus, this study indicates that both variables have a positive role. This means that a higher anchor virtues personality is associated with a higher level of flourishing. One limitation of this study is that it was conducted only among civil servant lecturers in Surakarta, with few respondents. Future researchers are encouraged to extend the study to a broader geographical area with a more diverse subject pool and explore other anchor elements, such as self, material, and others.